1989
DOI: 10.1136/thx.44.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the oesophagus in Transkei: treatment by intubation.

Abstract: The management of carcinoma of the oesophagus poses formidable logistic problems in countries such as Transkei where the condition is common and resources are limited. Most patients present late, often with complications, and are reluctant to undergo major surgery. Two hundred and fifty consecutive patients who presented over nine months in Transkei were studied. The incidence increased with age until 70 years and the disease occurred equally in men and women. The neoplasm was predominantly squamous cell (243 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Two case series 30,32 and five RCTs 53,54,56,57,60 reported outcomes of intubation with plastic stents. Operative mortality rates ranged from 0% to 27% 30,53,54,60 with median OS ranging from 12 to 19 weeks 32,54,56,57 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two case series 30,32 and five RCTs 53,54,56,57,60 reported outcomes of intubation with plastic stents. Operative mortality rates ranged from 0% to 27% 30,53,54,60 with median OS ranging from 12 to 19 weeks 32,54,56,57 .…”
Section: Resultsmentioning
confidence: 99%
“…20 Of the 37 nonrandomized studies, 17 reported on palliative luminal and surgical interventions ( Table 1). Ten of these studies reported on self-expandable metallic stents (SEMS) 6,[20][21][22][23][24][25][26][27][28] ; five on rigid plastic stents, laser treatment or dilation [29][30][31][32][33] ; and two on retrosternal gastric bypass. 34,35 Four studies reported on palliative radiotherapy, 18,20,32,36 six studies on chemotherapy 32,37-41 and three studies on concurrent chemoradiotherapy 32,42,43 (Table 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…These stents provided relief to dysphagia and symptoms of trachea-oesophageal fistula as well as improvement of nutritional status of patients but with high procedure-related mortality rate of between 15% and 40% and no long-term follow-up data. 58,59,60,61,62,63,64,65 The first study to use metal stents compared them to plastic stents and found metal stents to have superior efficacy but with greater cost. 66 Five studies investigating the palliation of malignant dysphagia using self-expanding metal stents (SEMS) were published after the year 2000.…”
Section: Mechanical Endoluminal Therapymentioning
confidence: 99%